How Adolescents Develop Responsibility: What Can Be Learned From Youth Programs. (September 2014) - Salusky, Ida; Larson, Reed W.; Griffith, Aisha; Wu, Joanna; Raffaelli, Marcela; Sugimura, Niwako; Guzman, Maria
<x xml:space="preserve">Abstract</x> This theory‐building qualitative study examined how youth develop responsibility within the context of organized youth programs. Interviews were conducted with ethnically diverse youth, parents, and adult leaders from four programs for high school–aged teens. Analysis suggested that youth develop responsibility through a four‐step cycle: (1) voluntarily taking on roles and obligations, (2) experiencing challenge and strain, (3) being motivated to fulfill their obligations, and (4) internalizing a self‐concept that leads to responsible behavior in other contexts. Leaders support this learning cycle by creating program structures and providing ongoing support that helps youth experience ownership of demanding roles. Peers contribute by providing a sense of solidarity while also imposing mutual accountability.